MEMORIZATION MODEL OF MNEMONICS METHOD IN LEARNING AKSARA SUNDA WRITING - Nurbaeti, Sri (2013)
This research background is the importance of learning model in teaching activity issue, the assumption that learning aksara sunda is difficult, and the researcher's anxiety of losing aksara sunda. This research aims to measure the effectivity of memorization model of mnemonics method in learning aksara sunda writing. The study used a quasi experiment and applying memorization model of mnemonics method. This research is done in 27 days, since November 1 - 27, 2012 in SMA Laboratorium-Percontohan Indonesia University of Education. The data was taken from writing aksara sunda study result of X-C Class student in SMA Laboratorium-Percontohan Indonesia University of Education terms 2012-2013. Total correspondents are 27 students, 15 boys and 12 girls. Test is the technic used in this research and the instrument is a written test. The findings reveal that (1) There is a distinction in students' skill before and after using memorization model of mnemonics method, (2) The test result shows a significant distinction in student's skill in writing aksara sunda before and after using memorization model of mnemonics, the skill increased from 48,61% to 82,50% with average 33, 89%, and (3) Hypotesis result is tscore (12,5) > ttable (2,48). It shows that alternative hypotesis (Ha) is accepted dan null hypothesis (Ho) is rejected. In conclusion, memorization model of mnemonics method is effectively used in learning aksara sunda writing. Keywords: Memorization model, Mnemonics Method, Aksara Sunda W